Rituximab treatment for difficult-to-treat nephrotic syndrome in children: a multicenter, retrospective study - ALPAY, HARİKA; YILDIZ, NURDAN (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Background/aim: This study aimed to evaluate the efficacy of rituximab in children with difficult-to-treat nephrotic syndrome, considering the type of disease (steroid-sensitive or -resistant) and the dosing regimen. Materials and methods: This multicenter retrospective study enrolled children with difficult-to-treat nephrotic syndrome on rituximab treatment from 13 centers. The patients were classified based on low (single dose of 375 mg/m(2)) or high (2-4 doses of 375 mg/m(2)) initial dose of rituximab and the steroid response. Clinical outcomes were compared. Results: Data from 42 children [20 steroid-sensitive (frequent relapsing / steroid-dependent) and 22 steroid-resistant nephrotic syndrome, aged 1.9-17.3 years] were analyzed. Eleven patients with steroid-sensitive nephrotic syndrome (55%) had a relapse following initial rituximab therapy, with the mean time to first relapse of 8.4 +/- 5.2 months. Complete remission was achieved in 41% and 36% of steroid-resistant patients, with the median remission time of 3.65 months. At Year 2, eight patients in steroid-sensitive group (40%) and four in steroid-resistant group (18%) were drug-free. Total cumulative doses of rituximab were higher in steroid-resistant group (p = 001). Relapse rates and time to first relapse in steroid-sensitive group or remission rates in steroid-resistant group did not differ between the low and high initial dose groups. Conclusion: The current study reveals that rituximab therapy may provide a lower relapse rate and prolonged relapse-free survival in the steroid-sensitive group, increased remission rates in the steroid-resistant group, and a significant number of drug-free patients in both groups. The optimal regimen for initial treatment and maintenance needs to be determined.
Keywords: Frequently relapsing nephrotic syndrome; immunosuppressive agents; steroid-dependent nephrotic syndrome; steroid-resistant nephrotic syndrome; remission; CHILDHOOD-ONSET; FOLLOW-UP; CYCLOSPORINE